Noncollinear Korringa-Kohn-Rostoker Green function method: Application to 3d nanostructures on Ni(001) - Lounis, S.; P. Mavropoulos; P.H. Dederichs; Blugel, S (PHYSICAL REVIEW B, 2005)
Magnetic nanostructures on nonmagnetic or magnetic substrates have attracted strong attention due to the development of interesting experimental methods with atomic resolution. Motivated by this progress we have extended the full-potential Korringa-Kohn-Rostoker Green-function method to treat noncollinear magnetic nanostructures on surfaces. We focus on magnetic 3d impurity nanoclusters, sitting as adatoms on or in the first surface layer on Ni(001), and investigate the size and orientation of the local moments and, moreover, the stabilization of noncollinear magnetic solutions. While clusters of Fe, Co, Ni atoms are magnetically collinear, noncollinear magnetic coupling is expected for Cr and Mn clusters on surfaces of elemental ferromagnets. The origin of frustration is the competition of the antiferromagnetic exchange coupling among the Cr or Mn atoms with the antiferromagnetic (for Cr) or ferromagnetic (for Mn) exchange coupling between the impurities and the substrate. We find that Cr and Mn first-neighboring dimers and a Mn trimer on Ni(001) show noncollinear behavior nearly degenerate with the most stable collinear configuration. Increasing the distance between the dimer atoms leads to a collinear behavior, similar to the one of the single impurities. Finally, we compare some of the noncollinear ab initio results to those obtained within a classical Heisenberg model, where the exchange constants are fitted to total energies of the collinear states; the agreement is surprisingly good.